ETHNOPSYCHOLOGICAL PRINCIPLES OF FAMILY TRADITIONS IN UZBEK FAMILIES (ResearchJet Journal of Analysis and Inventions, 2021)
This article describes the level of importance of the family tree of the Uzbek family, the ethnopsychological principles of family traditions and methods of application of national ethnopsychological features of the Uzbek people in family upbringing.